2014
DOI: 10.1002/etc.2623
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigations on C60–ionic liquid interactions and their impacts on C60 dispersion behavior

Abstract: Increased use and production of carbon nanomaterials (e.g., fullerene C60 ) and ionic liquids (ILs) may result in their concomitant releases into the environment. Inevitably there will be interactions between carbon nanoparticles (CNPs) and ILs. However, experimental data on the interaction of CNPs with ILs are not readily available, and the mechanism behind the interactions is still elusive. To contribute to an understanding of the molecular interactions established between CNPs and ILs, theoretical investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Analogous results were reported by Wang et al 56 55 showed that for 43 (cation further of C60 than anion) but not for Wang et al 55 There is a discrepancy for the anion and cation RDFs first peak intensity, g(R 1 ), in the case of [BMIM][BF 4 ], Wang et al 55 reports g(R 1 ) larger for the cation than for the anion, whereas Maciel and Fileti 43 reported the reverse behavior in agreement with results reported in this work, Figure 4 and Table 2. Moreover, Wang et al 55 reports larger g(R 1 ) values for the cation than for the anion for all the six ILs studied.…”
Section: Molecular Dynamicssupporting
confidence: 88%
“…Analogous results were reported by Wang et al 56 55 showed that for 43 (cation further of C60 than anion) but not for Wang et al 55 There is a discrepancy for the anion and cation RDFs first peak intensity, g(R 1 ), in the case of [BMIM][BF 4 ], Wang et al 55 reports g(R 1 ) larger for the cation than for the anion, whereas Maciel and Fileti 43 reported the reverse behavior in agreement with results reported in this work, Figure 4 and Table 2. Moreover, Wang et al 55 reports larger g(R 1 ) values for the cation than for the anion for all the six ILs studied.…”
Section: Molecular Dynamicssupporting
confidence: 88%
“…Forcite Plus code was used to obtain the initial optimized structures of the studied systems at a molecular mechanics level [13][14][15][16]. The atomic configuration with the lowest total energy for each system was built as a set of inputs for geometry optimization and properties calculation at a quantum mechanics level.…”
Section: Density-functional Theory Calculationsmentioning
confidence: 99%
“…There is a growing interest in exploring various computational approaches to better understand and generalize the fate and behavior of NPs in aqueous suspensions [17][18][19][20][21][22][23][24][25]. Brownian dynamics, molecular dynamics, and Monte Carlo simulations have been applied to analyze the details of NP agglomeration kinetics and agglomerate morphology [17,26,27].…”
Section: Introductionmentioning
confidence: 99%